The human L-myc gene is expressed as two forms of protein in small cell lung carcinoma cell lines: detection by monoclonal antibodies specific to two myc homology box sequences. - Ikegaki, N (1989)
The L-myc gene is the third member of the myc family of proto-oncogenes. Amplification and elevated expression of the L-myc gene has been detected in a subset of small cell lung carcinoma (SCLC) cell lines. The biological properties and functions of the L-myc gene and its product have not yet been elucidated. Monoclonal antibodies against two myc homology boxes were used to characterize the L-myc gene product. These antibodies react with two groups of polypeptides of apparent masses of 60, 61 and 66 kd (the long forms), and 34 and 37 kd (the short forms) in SCLC cells expressing L-myc transcripts. The long form L-myc proteins are associated with the nuclear fraction of the cells. The short form L-myc proteins are present in the cytoplasmic fraction, though diffusion of the short forms from the nucleus during cell fractionation cannot be ruled out. The half-life of the long form polypeptides is approximately 45-90 min. The short form polypeptides have a half-life of approximately 120-180 min. The L-myc protein is not detectable in the mitotic cells, suggesting that the L-myc protein expression is tightly regulated during the cell cycle.